2013
DOI: 10.1155/2013/926942
|View full text |Cite
|
Sign up to set email alerts
|

2-Heptyl-Formononetin Increases Cholesterol and Induces Hepatic Steatosis in Mice

Abstract: Consumption of isoflavones may prevent adiposity, hepatic steatosis, and dyslipidaemia. However, studies in the area are few and primarily with genistein. This study investigated the effects of formononetin and its synthetic analogue, 2-heptyl-formononetin (C7F), on lipid and cholesterol metabolism in C57BL/6J mice. The mice were fed a cholesterol-enriched diet for five weeks to induce hypercholesterolemia and were then fed either the cholesterol-enriched diet or the cholesterol-enriched diet-supplemented form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In contrast, HDL-cholesterol tends to carry cholesterol away from the arteries to the liver. Thus, an increase in HDL-cholesterol protects against cardiovascular diseases [25,26]. This result showed that CuAE could have some beneficial effects by reducing cardiovascular risk factors.…”
Section: Test Groups Satellite Groupsmentioning
confidence: 99%
“…In contrast, HDL-cholesterol tends to carry cholesterol away from the arteries to the liver. Thus, an increase in HDL-cholesterol protects against cardiovascular diseases [25,26]. This result showed that CuAE could have some beneficial effects by reducing cardiovascular risk factors.…”
Section: Test Groups Satellite Groupsmentioning
confidence: 99%
“…Likewise, a mixture of polyphenols, containing resveratrol, genistein, and quercetin, increased hepatic lipids but did not activate expression of genes relative to apoptosis, cell repair, or tissue remodeling (Miller et al, ). Also, formononetin, an O ‐methylated isoflavone, decreased liver weight, inflammation, and injury but simultaneously increased plasma triglyceride levels and caused hepatic steatosis (Andersen et al, ). As expected, hepatic steatosis was associated with downregulation of fatty acid β ‐oxidation genes ( Atgl , Cpt1a , Acox1 , and Acat2 ) and the microsomal triglyceride transfer protein, a gene that is responsible for lipoprotein assembly and export from the liver (Andersen et al, ).…”
Section: Treatment Of Non‐alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Also, formononetin, an O ‐methylated isoflavone, decreased liver weight, inflammation, and injury but simultaneously increased plasma triglyceride levels and caused hepatic steatosis (Andersen et al, ). As expected, hepatic steatosis was associated with downregulation of fatty acid β ‐oxidation genes ( Atgl , Cpt1a , Acox1 , and Acat2 ) and the microsomal triglyceride transfer protein, a gene that is responsible for lipoprotein assembly and export from the liver (Andersen et al, ). Why in these studies isoflavones prevent hepatic inflammation and injury (i.e., NASH) without suppressing hepatic steatosis is not clear, but different signaling pathways that isoflavones interact with may be the reason.…”
Section: Treatment Of Non‐alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Formononetin, another active compound of Radix Astragali, has been reported to be able to decrease markers of inflammation and liver injury in a cholesterol-enriched diet-induced hepatic steatosis C57BL/6J mice model. 36 Formononetin can be metabolized into formononetin glucuronide in the colon by uridine 5 0 -diphospho-glucuronosyl transferases (UGTs) 37 and, again, bacteria expressing high concentrations of glucuronidases can release formononetin from formononetin glucuronide to exert bioactive effects.…”
Section: Discussionmentioning
confidence: 99%